Introducing computers concepts & applications ([Belmont, CA], 2006)
A sneak peak at Microsoft office 2007, Shelly Cashman series, New perspectives series, Illustrated series, Additional series, SAM, Course.com, Higher level solutions....
Keywords: Computers; Electronic digital computers; Electronic data processing